Active Sites Regulation for High-Performance Oxygen Evolution Reaction Electrocatalysts - Tang, Yu; Zhang, Tianyi; Wu, Xuan; Deng, Shukang (Frontiers in Chemistry, 2022)
Electrochemical water splitting to produce molecular hydrogen and oxygen provides a promising strategy engineering for scalable hydrogen production with high purity. Unfortunately, the sluggish kinetics of oxygen evolution reactions (OER) due to the interdependence multiple steps procedure require high overpotential to achieve appreciable catalytic current density, resulting in relatively low energy conversion efficiencies. Therefore, development of high-performance OER electrocatalysts is vital to drive the commercial application of water splitting. This review highlights current progress of representative catalyst electrocatalysts in the past decade. Active sites regulation for excellent OER performance of precious metals single atoms catalyst, high-entropy alloy, transition metals oxides, transition metal chalcogenide are emphasized. And a more in-depth exploration of OER reaction mechanism by in situ technique and DFT results will be conducted. This review can provide the basis for the development and modification of OER electrocatalysts.